Use of waste animal blood as a bio-based air-entraining additive in the production of sustainable hydraulic lime-based grouts - Dinc-Sengonul, Burcu; Boylu, Selen; Yuzer, Nabi (ELSEVIER, 2026)
This study investigates waste animal blood (WAB) as a bio-based air-entraining admixture for natural hydraulic lime (NHL5) grouts. The protein- and surfactant-rich composition of WAB is hypothesized to entrain and stabilize micro-air voids, thereby disrupting capillary continuity, reducing the capillary absorption coefficient, and enhancing resistance to freeze-thaw deterioration. Four formulations containing 0-2.0 % WAB (w/b = 0.65) were evaluated for fresh-state behaviour, rheology, setting, capillary absorption, contact angle, pore structure (MIP), microstructure (SEM-EDS, FTIR/XRD), mechanical strength, and freeze-thaw durability. The incorporation of WAB lowered yield stress and plastic viscosity, prolonged setting, and improved injectability. At 90 days, capillary absorption decreased by up to similar to 63 %, while contact angles increased from 0 degrees to similar to 100-127 degrees, indicating a shift from hydrophilic to hydrophobic behaviour. MIP analyses revealed higher total porosity but fewer fine, interconnected capillary pores, consistent with a reduction in the capillary absorption coefficient and increased air entrainment. Compressive strength decreased by similar to 24 % at 2.0 % WAB due to coarser pore structures. After 14 freeze-thaw cycles, WAB-modified grouts showed lower mass loss and greater retention of ultrasonic pulse velocity, confirming improved freeze-thaw resistance. Overall, WAB represents an environmentally beneficial strategy for modifying rheology and moisture transport in lime-based grouts, supporting the development of sustainable, waste-derived materials for heritage conservation.
Keywords: Bio-based air-entraining additive; Lime-based grouts; Masonry preservation; Sustainability; Waste animal blood (WAB); RHEOLOGICAL PROPERTIES; WATER-CONTENT; MORTARS; INJECTION; TEMPERATURE; STRENGTH; FRESH; SUPERPLASTICIZER; CONSOLIDATION; RESTORATION; Engineering